Answering Jewish objections to Jesus ; v. 3 Messianic prophecy objections - Brown, Michael L. 1955- (Grand Rapids, MI Baker, 2003)
Includes bibliographcial references and indexes.
Keywords: Apologetics; Jews -- conversion to Christianity; Jesus Christ -- Messiahship